Analisis Biaya Operasional Kapal untuk Penentuan Tarif Transportasi Sungai dan Pesisir di Kabupaten Paser, Kalimantan Timur - Muhammad Hadid; Priyo Wibisono (Departemen Teknik Infrastruktur Sipil Institut Teknologi Sepuluh Nopember Surabaya, 2022)
This study aims to obtain river and coastal transportation tariff in Paser Regency, which connects Tanah Grogot (Senaken), Muara Paser, and Tanjung Aru. Determining the tariff for river and coastal transportation is based on the Regulation of the Minister of Transportation of the Republic of Indonesia Number PM 66 of 2019. The tariff is determined based on the Operational Cost (OC) and the distance traveled by river and coastal transportation services. The ship used in this study is a wooden boat weighing 40 GT that can accommodate passengers and motorcycle/two-wheeled vehicles. The tariff determination considers the load factor of 60%. The results show that the BOK per year for river and coastal transportation is Rp. 874,495,665. The river transportation tariff for the Tanah Grogot (Senaken) – Muara Paser route for passengers and two-wheeled vehicles/motorcycles is Rp. 19,101 and Rp. 14,824, respectively. Meanwhile, the tariff for passengers and two-wheeled vehicles/motorcycles for the Senaken – Tanjung Aru route is Rp. 47,752. and Rp. 37,061, respectively. Determination of the load factor in setting tariffs depends on the potential demand that will use transportation and can consider how policy regulators can provide subsidy allocation.